Criminal Investigation of the Corruption Crimes: Evidence and Procedure in an Interdisciplinary Approach - Delia Magherescu (Revista Brasileira de Direito Processual Penal)
Approaching criminality in an interdisciplinary context has concerned practitioners in the last decades. The same situation is observed in criminal cases having as object the criminal investigation of corruption crimes, knowing the fact that this phenomenon is still into the judicial authorities' attention. In practice, there is a substantial jurisprudence on this topic. The current paper focuses on criminal investigation of the corruption in an interdisciplinary context, including elements of forensic investigation, gathering evidence by means of forensic science, as well as their administration during the criminal proceedings. Moreover, researching the current topic aims at analyzing phenomenon from the perspective of the judicial bodies' efforts of assuring functions of discovering and preventing corruption crimes, as well as punishing defendants during the criminal proceedings. In order to achieve this goal, the paper is designed in a qualitative research, with comparative elements and aspects of jurisprudence in criminal matters.